PENGARUH PEMBANGUNAN ZONA INTEGRITAS, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEBUTUHAN BERPRESTASI DAN KINERJA PEJABAT STRUKTURAL PENGADILAN AGAMA DI NUSA TENGGARA TIMUR - Saiin Ngalim; Meutia Meutia; A.A Ketut Budiastra (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to analyze the effect of the Development of Integrity Zones, Compensation and Work Environment on the need for achievement and the Performance of Struktural Officials of the Religious Courts in East Nusa Tenggara. Data were obtained using a closed statement questionnaire on a likert scale of 1 to 6 on five research variabels. The number of respondents 91 people. Data were analyzed using Struktural Equation Modeling (SEM) based on variance (Partial Least Square) with SmartPLS software version 3 for Windows. Hypothesis testing for alpha 5% is accepted if the t statistic is > 1.96 or p values ??< 0.05. The results of the study show that (1). The Development of the Integrity Zone has a positive but not significant effect on the need for achievement, (2). Compensation has a negative and insignificant effect on the need for achievement. (3) The work environment has a positive but not significant effect on the need for achievement. (4) The development of the Integrity Zone has a positive and significant effect on performance. (5) Compensation has a positive and significant effect on performance. (6) Work environment has a negative and insignificant effect on performance. (7) The need for achievement has a positive and insignificant effect on performance. (8) The role of the need for achievement in mediating the effect of the Integrity Zone Development on performance is a no mediation effect (does not have a mediating effect). (9) The role of the need for achievement in mediating the effect of compensation on performance is a no mediation effect. (10) The role of the need for achievement in mediating the effect of the work environment on performance is a no mediation effect